El baile de salón como una ocupación significativa para los ancianos - dos Santos, Nathila Alexandre; Reinoso Araujo de Carvalho, Claudia (Revista Chilena de Terapia Ocupacional, 2021)
Occupations play an important role in the quality of life of the elderly people. The ballroom dancing could be a significant occupation for them. This study aimed to analyze ballroom dancing in its form, function and meaning. It is about an experience report, which was considered experiences with elderly people in gyms and ballroom dancing during the period from July 2014 to May 2018. Preceded by general considerations about ballroom dancing, the information was categorized and discussed around following aspects: the effects of ballroom dancing on health; the ballroom dance in the social context of the seniors; the relationship between ballroom dancing and self-esteem; the relationship between ballroom dancing and sexuality. It has been observed that ballroom dancing has a positive impact on health, contributes to the increase the social life of the elderly participants, as well as their self-esteem and the practice of their sexuality. It is concluded that dance could favor successful old age, it contributes maintaining independence and active involvement with social life. Although the meanings of occupations are subjective, dance could be considered an activity ,that if regularly practiced, could produce meaning to existence, to enhance social life and contribute to personal satisfaction and disease prevention.